Adaptation of athletes` cardiorespiratory system to physical loads - Vanyushin, Yu. S.; Khairullin, R. R.; Elistratov, D. E.; Fedorov, N. A.; Ishmukhametova, N. F. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze the peculiarities of adaptation of the cardiorespiratory system of athletes engaged in endurance sports. Methods and structure of the study. The study involved a set of non-invasive research methods. Besides, we tested the athletes` cardiovascular, external respiration and gas exchange systems. Results of the study. Among the physiological determinants of the cardiorespiratory system are: inotropic, chronotropic, vascular and respiratory reactions, the activation of which depends on the functional loads. During active orthostasis, a whole array of cardiorespiratory functional elements take part in the compensatory-adaptive reactions, with no driving factor to be distinguished. Under physical loads from 50 to 200 W, there was a decline in the growth in cardiac output, which, depending on the athletes` age, was compensated by one of the cardiorespiratory system reactions: external respiration, blood circulation or gas exchange function. By the prevailing nature of individual reactions of the circulatory and respiratory organs, the types of adaptation of the cardiorespiratory system were identified. Under the maximum load (3 W/kg), a mixed type of reaction was observed, which was characterized by an increase to the individual limit of indicators of the chronotropic function of the heart, external respiration and, in some cases, stroke output. Conclusion. The functional system structure is characterized by constant changes in the degree of involvement of its functional elements and peculiarities of their combination.